2018
DOI: 10.21037/jtd.2018.03.70
|View full text |Cite
|
Sign up to set email alerts
|

Effects of para-toluenesulfonamide intratumoral injection on pulmonary adenoid cystic carcinoma complicating with severe central airway obstruction: a 5-year follow-up study

Abstract: Pulmonary adenoid cystic carcinoma (ACC) is a rare type of non-small cell lung carcinoma that may develop life-threatening severe malignant airway obstruction (SMAO). Currently, limited therapeutic approaches exist for ACC-SMAO. We investigated the efficacy and safety of para-toluenesulfonamide (PTS) intratumoral injection for ACC-SMAO. In this phase III, multicenter, non-randomized, single-arm, openlabel trial, we recruited eight hospitalized patients with ACC-SMAO between October 2009 and January 2011. Withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The side effect profile was otherwise tolerable and the study confirmed the anti-tumour effect of PTS in NSCLC. A 5-year follow up study analysing a subset of these patients with adenoid cystic carcinoma of the lung suggested similar safety and clinical benefits of intratumoural PTS [32].…”
Section: Recent Trials In Bronchoscopic Intratumoural Injectionmentioning
confidence: 87%
See 2 more Smart Citations
“…The side effect profile was otherwise tolerable and the study confirmed the anti-tumour effect of PTS in NSCLC. A 5-year follow up study analysing a subset of these patients with adenoid cystic carcinoma of the lung suggested similar safety and clinical benefits of intratumoural PTS [32].…”
Section: Recent Trials In Bronchoscopic Intratumoural Injectionmentioning
confidence: 87%
“…Since then, many different experimental agents have been delivered to lung tumours via transbronchial needle injection (TBNI) including chemotherapy [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], gene therapies [35][36][37][38][39][40][41][42][43][44], and other immune adjuvants [13,14,45,46] (see table 1). These studies have established feasibility of local injection, and side effects have overall been minimal.…”
Section: History Of Intratumoural Therapies For Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The dosage of cisplatin used here was based on studies investigating how this drug affects apoptosis, invasion, metastasis, angiogenesis, and the growth signal mechanisms in canine melanomas implanted in mice [ 24 ]. We based the PTS dosage on the dose that is generally used to treat lung cancer [ 12 ], and the route of PTS administration was according to that reported in various studies [ 12 , 13 , 94 , 98 ]. We assessed the growth of the tumors every 7 days by measuring their largest and smallest diameters and calculated their volume according to the following formula: V = 0.5 × a × b 2 , where a and b are the largest and smallest diameters, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Para -toluenesulfonamide is a simple small molecule displaying both in vitro and in vivo anticancer activities in a variety of cancers including lung cancer, prostate cancer and tongue squamous cell carcinoma [ 13 , 14 , 15 ]. The clinical trials show that para -toluenesulfonamide displays efficient anti-tumor activity against advanced hepatocellular carcinoma and non-small cell lung cancer through a concurrent local injection therapy [ 16 , 17 , 18 , 19 ]. Recently, we have demonstrated that para -toluenesulfonamide is a potential anti-tumor agent which inhibits both the Akt-dependent and -independent mammalian target of rapamycin (mTOR)/p70S6 kinase (p70S6K) pathways in prostate cancers, and the disturbance of lipid raft and cholesterol contents also are involved in the para -toluenesulfonamide-mediated mechanism [ 15 ].…”
Section: Introductionmentioning
confidence: 99%